Quantum Performance at its best - Lebese, Mokone, Solomon (My University, 2022)
The idea of training is based on a number of assumptions that are sound and verifiable. One of these assumptions is the law of cause effect. According to this law nothing happens without a cause. In order for something to become, there must be an originator or an inventor or a cause. This concept is supported by the adage: ‘There is no smoke without fire.’ Also, many believe that the disasters in our planetary system cannot just happen, but must be the result of some cause. Hence they are called acts of God. If they are acts, it follows that somebody is doing something to cause effects. If disasters are acts of God, what about other creations and marvels in our orderly planetary system and specifically on our planet home? The most dynamic and undeniable assumption is that of the body. It has been marvelously designed with organs that show that there is no reaction without an outside cause. The presence of the ears, nose, eyes, taste and touch in the body confirm that these organs are poised to be activated by sensations from outside. These sensations could be called inputs because they come from outside. The birth of a child is another powerful support for effects from outside-in. No pregnancy can take place without insemination or sexual intercourse. The story of the virgin birth has been denied by many because of their strong adherence to the concept of cause-effect relationships. It is an accepted notion that if a woman is pregnant, someone must be responsible for that pregnancy. Should it happen that one could see a car in the highway at great speed without a driver, that event would be news-paper headlines the next day. This is because no car can travel without a driver. This is the whole basis of training and development in any sphere of life. With that said, let us examine the anatomy of a training and development strategy for Year 2000 and beyond – The WORD-ACAID SYSTEM PHILOSOPHY
Keywords: Ideas; Linguistics; Management and Leadership; Performance; Personal Development; Thinking and Decisiveness